1981
DOI: 10.1159/000198597
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Active Hepatitis and Giant Multinucleated Hepatocytes in Adults Treated with Clometacin

Abstract: The authors report the cases of 2 adults who became jaundiced during prolonged administration of clometacin, a new analgesic drug. Jaundice and serum aminotransferase activity progressively increased while the drug administration was continued but quickly decreased when it was eventually interrupted. 1 patient resumed the intake of clometacin and died with jaundice and ascites. In both patients, liver lesions were those of severe chronic active hepatitis with numerous giant multinucleated hepatocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In addition to medications, such as clometacin, 50 diclofenac, 51 doxycycline, 11 , 17 amoxicillin/clavulanate, 12 dehydrocholic acid, 11 and testosterone analogue, 52 herbal remedies, 53 55 and dietary supplements 56 were also reported to have an association with PIGCH. The most commonly associated malignancy with PIGCH appeared to be chronic lymphocyte leukemia (CLL).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to medications, such as clometacin, 50 diclofenac, 51 doxycycline, 11 , 17 amoxicillin/clavulanate, 12 dehydrocholic acid, 11 and testosterone analogue, 52 herbal remedies, 53 55 and dietary supplements 56 were also reported to have an association with PIGCH. The most commonly associated malignancy with PIGCH appeared to be chronic lymphocyte leukemia (CLL).…”
Section: Resultsmentioning
confidence: 99%
“…Instead, they had the appearance of active cells with abundant endoplasmic reticulum and numerous mitochondria, thus indicating that giant multinucleated hepatocytes were regenerative rather than degenerative cells, and the formation of giant multinucleated hepatocytes was due to nuclear division without cytoplasmic division. 50 However, in PIGCH associated with HCV, CLL, 37 and autoimmune hepatitis, 23 giant cells were strongly positive for keratin 8/18 (mature hepatocyte marker) and cyclin D1 (G1 phase marker), 37 and negative for Ki-67 (proliferation marker) and keratin 19/keratin 7 (intermediate hepatocyte makers), 23 hence indicating that nuclear division was a less likely explanation for the giant cell formation. On the other hand, the identification of intracellular plasma membrane remnants in the giant multinucleated hepatocytes indicated that the fusion of hepatocytes was a more likely mechanism for giant cell formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug-induced autoimmune hepatitis (DIAH) has been reported for a number of agents (5), the most common of which are currently methyldopa (6-8), nitrofurantoin (9)(10)(11)(12)(13)(14), minocycline (15)(16)(17)(18)(19)(20)(21), and clometacin (22,23). Interferon is increasingly being cited as a possible cause (24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the liver lesion characterized by formation of multinucleated hepatocytes is often found in neonates and infants and is called post-infantile giant cell hepatitis(PIGCH) [5], whereas it is very rare in adults. The cause of PIGCH has been considered to be viral infection [7,8], drug intoxication [6,8], or autoimmunity [1,3], but it is still obscure in some cases [4,8]. On the other hand, reports of giant cell hepatitis are strikingly few in animals [2].…”
mentioning
confidence: 99%